3D fungi carbon by less-alkali activation for supercapacitors. (November 2020) - Zheng, Yujing; Lian, Yue; Wang, Dawei; Ban, Chaolei; Zhao, Jing; Zhang, Huaihao
Abstract: In recent years, the green synthesis of porous carbon electrode materials with high specific surface area has aroused extensive research. In this work, the dictyophora with special inherent structure was employed to prepare porous activated carbon (DHC) by hydrothermal carbonization. Compared with traditional alkali activation, the activation temperature used in this work is lower. The resultant 3D porous carbon, rich in N and O elements, can provide large active surface area, pseudo-capacitance and good electrochemical behavior. Specifically, DHC has high charge storage capacity (up to 310.5 F g −1 at 0.5 A g −1 ), good rate capability (85.4% from 0.5 A g −1 to 10 A g −1 ) and excellent cycle stability (96.1% after 5000 cycles). Graphical abstract: The dictyophora hydrothermal carbon (DHC), prepared by green activation, has 3D porous structure and abundant N, O functional groups, which can provide large active surface area and good electrochemical performance. Image 1 Highlights: The green synthesis is used to reduce the harm to the instrument and the environment, and the resultant heteroatomic functional groups are more reserved in carbon. The 3D structure of DHC contains abundant N and O functional groups, helpful to improve the wettability and redox reactivity of the material surface. The asembled supercapacitors has high charge storage capacity, good rate capability and excellent cycle stability.